2018
DOI: 10.1007/s00590-018-2190-2
|View full text |Cite
|
Sign up to set email alerts
|

Delay in weight bearing in surgically treated tibial shaft fractures is associated with impaired healing: a cohort analysis of 166 tibial fractures

Abstract: BackgroundThe relation between timing of weight bearing after a fracture and the healing outcome is yet to be established, thereby limiting the implementation of a possibly beneficial effect for our patients. The current study was undertaken to determine the effect of timing of weight bearing after a surgically treated tibial shaft fracture.Materials and methodsSurgically treated diaphyseal tibial fractures were retrospectively studied between 2007 and 2015. The timing of initial weight bearing (IWB) was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
(42 reference statements)
2
25
0
1
Order By: Relevance
“…This nding may be explained by a relationship between weight bearing and healing outcomes in the reverse direction. That is, bone non-union may cause more pain, resulting in delayed weight bearing, rather than delayed weight bearing causing non-union [37]. Additionally, internal xation failure is often considered as a reason to postpone the initial weight bearing.…”
Section: Resultsmentioning
confidence: 99%
“…This nding may be explained by a relationship between weight bearing and healing outcomes in the reverse direction. That is, bone non-union may cause more pain, resulting in delayed weight bearing, rather than delayed weight bearing causing non-union [37]. Additionally, internal xation failure is often considered as a reason to postpone the initial weight bearing.…”
Section: Resultsmentioning
confidence: 99%
“…After surgery patients were treated with culture specific antibiotics for 12 weeks (7-14 days intravenous, completed with oral antibiotics) depending on pathogen and clinical evolution. During rehabilitation, permissive weight baring was allowed to improve healing [10] .…”
Section: Treatment Algorithmmentioning
confidence: 99%
“…This is an open access article under the CC BY-NC-ND license ( http://creativecommons.org/licenses/by-nc-nd/4.0/ ) [ 6 , 7 ]. Open fractures, bone loss, smoking, NSAIDs usage, delay of weight baring and insufficient fixation are important risk factors and can cause a significant risk increase for non-union [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, clinical data have demonstrated benefit of physical therapy to improve functional outcomes following most musculoskeletal injuries. For instance, early weight bearing is recommended for simple mid-shaft tibia fractures operatively managed with open reduction internal fixation with an intramedullary nail [86]; corresponding with retrospective evidence that delayed initial weight bearing following open and closed tibia diaphyseal fractures associates with increased risk of non-union [87]. As another example, a prospective randomized control trial demonstrated benefit of using an active controlled motion device in addition to a standard physical therapy targeted at early partial weight-bearing for isolated unstable ankle fractures (i. e. Weber type B-or C-Fracture) [88].…”
Section: General Efficacy Of Physical Therapymentioning
confidence: 99%